Group Psychoeducation and Academic Buoyancy: A Pilot Comparison of Role-Playing and Self-Instruction Techniques - Hadziq Muhibbuddin; M Muslikah (KONSELOR, 2026)
Academic buoyancy refers to a student’s ability to persevere and recover from daily academic challenges such as assignments, evaluations, and performance pressures. It is especially vital during adolescence, particularly for high school students, as it supports academic success and helps them adapt. This study examines how group psychoeducation—using role-playing and self-instruction techniques—can improve high school students’ academic buoyancy. A quasi-experimental design with repeated measures was used, involving two groups: one using role-playing and the other self-instruction, each with seven students. Participants were purposively selected and randomly assigned to groups. Each group attended six 90-minute sessions. Academic buoyancy was assessed at three points—before, immediately after, and two weeks post-intervention—using the Academic Buoyancy Scale (ABS). Results from a Mixed ANOVA showed significant increases in buoyancy scores from pretest to posttest in both groups (p < .001), with a large effect size (ηp² = 1.000). The main effect of group was also significant (p < .001; ηp² = .679), indicating differences in effectiveness between the two methods. A significant interaction between time and group (p = .031; ηp² = .333) revealed differing patterns of improvement over time. These results confirm that both techniques improve academic buoyancy, though their effects vary in magnitude and duration.